2019
DOI: 10.1063/1.5093220
|View full text |Cite
|
Sign up to set email alerts
|

Screening billions of candidates for solid lithium-ion conductors: A transfer learning approach for small data

Abstract: Machine learning (ML) methods have the potential to revolutionize materials design, due to their ability to screen materials efficiently. Unlike other popular applications such as image recognition or language processing, large volumes of data are not available for materials design applications. Here, we first show that a standard learning approach using generic descriptors does not work for small data, unless it is guided by insights from physical equations. We then propose a novel method for transferring suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 33 publications
(41 reference statements)
0
114
0
1
Order By: Relevance
“…The combined database and machine learning approach have been applied to design and predict the material properties of electrodes such as voltage, crystallinity and chemical stability, from atomic scale to mesoscale 83,[94][95][96][97][98][99] . In addition, such an approach has been applied to design new liquid electrolytes and additives [100][101][102][103][104][105] , and solid-state electrolytes with fast Li-ion transport [106][107][108] and mechanical 82 properties. Such computational techniques provide an opportunity for exploring material properties at a lower cost and accelerating the material discovery processes.…”
Section: Future Outlook and Opportunitiesmentioning
confidence: 99%
“…The combined database and machine learning approach have been applied to design and predict the material properties of electrodes such as voltage, crystallinity and chemical stability, from atomic scale to mesoscale 83,[94][95][96][97][98][99] . In addition, such an approach has been applied to design new liquid electrolytes and additives [100][101][102][103][104][105] , and solid-state electrolytes with fast Li-ion transport [106][107][108] and mechanical 82 properties. Such computational techniques provide an opportunity for exploring material properties at a lower cost and accelerating the material discovery processes.…”
Section: Future Outlook and Opportunitiesmentioning
confidence: 99%
“…Moreover, not limited to perovskites, τ can also estimate the stability of perovskite‐like structures. Ekin et al demonstrated that the standard ML approach cannot establish suitable models from small data. To solve the problem of limited data, they created a transfer learning approach which combines structural models and elemental models.…”
Section: Basic Procedures Of ML In Materials Sciencementioning
confidence: 99%
“…High‐throughput screening methods have been used to explore ideal solid electrolytes. For small training data, Ekin et al revealed a kind of transfer learning methods to screen potential solid lithium‐ion conductors. In order to reduce the consumption of DFT calculations, Sokseiha and the coworkers proposed a new predictor related with high ionic conductivity that can be used in high‐throughput screening.…”
Section: Achievements Of ML In Energy Storage and Conversion Materialsmentioning
confidence: 99%
“…The sampling efficiency of iQSPR-X is highly influenced by the reliability of the evaluator that predicts the material properties for any given chemical structure. [18,[34][35][36][37][38][39][40][41] In this study, we applied a specific type of transfer learning using pre-trained neural networks. XenonPy currently provides 140,000 pretrained neural networks for the prediction of physical, chemical, electronic, thermodynamic, and mechanical properties of small organic molecules, polymers, and inorganic crystalline materials, with models for 15, 18, and 12 properties of these material types, respectively.…”
Section: Full Papermentioning
confidence: 99%
“…Other studies have also shown promising applications of transfer learning in materials informatics. [18,[34][35][36][37][38][39][40][41] In this study, we applied a specific type of transfer learning using pre-trained neural networks. For a target property, a neural network pre-trained on proxy properties is available in the library, where the source datasets are sufficiently large.…”
Section: Full Papermentioning
confidence: 99%